Cytokinins as key regulators in plant–microbe–insect interactions: connecting plant growth and defence. (12th February 2013) - Giron, David; Frago, Enric; Glevarec, Gaëlle; Pieterse, Corné M. J.; Dicke, Marcel; Biere, Arjen
Summary Plant hormones play important roles in regulating plant growth and defence by mediating developmental processes and signalling networks involved in plant responses to a wide range of parasitic and mutualistic biotic interactions. Plants are known to rapidly respond to pathogen and herbivore attack by reconfiguring their metabolism to reduce pathogen/herbivore food acquisition. This involves the production of defensive plant secondary compounds, but also an alteration of the plant primary metabolism to fuel the energetic requirements of the direct defence. Cytokinins are plant hormones that play a key role in plant morphology, plant defence, leaf senescence and source–sink relationships. They are involved in numerous plant–biotic interactions. These phytohormones may have been the target of arthropods and pathogens over the course of the evolutionary arms race between plants and their biotic partners to hijack the plant metabolism, control its physiology and/or morphology and successfully invade the plant. In the case of arthropods, cytokinin‐induced phenotypes can be mediated by their bacterial symbionts, giving rise to intricate plant–microbe–insect interactions. Cytokinin‐mediated effects strongly impact not only plant growth and defence but also the whole community of insect and pathogen species sharing the same plant by facilitating or preventing plant invasion. This suggests that cytokinins (CKs) are key regulators of the plant growth‐defence trade‐off and highlights the complexity of the finely balanced responses that plants use while facing both invaders and mutualists.